Implementation of the KADISA Program for Developing Elementary School Students’ Competence in Salat Recitations and Pillars: A Single-Case Study - Abubakar, Firah; Luthfiyah, Luthfiyah; Ihlas, Ihlas; Salmin, Salmin (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study analyzes the implementation of the KADISA “Kakidi Sambea” Program at SDN 05 (Public Elementary School 05) in Rabangodu Utara Urban Village, Bima City, in developing students’ competence in salat recitations and pillars, as well as the observed changes in their knowledge, attitudes, and practices. Design/methods/approach – This study employed a qualitative single-case study design from January to June 2026. The 20 participants comprised one school principal, four Islamic Religious Education teachers, three classroom teachers, and 12 purposively selected students in Grades IV to VI. Data were collected through 24 participant observation sessions, in-depth interviews, and document analysis. The data were analyzed iteratively through data reduction, data display, conclusion drawing and verification, inductive and deductive coding, and source and method triangulation. Findings – The program was implemented through planning, the allocation of teacher roles, daily habituation, recitation and movement practice, collective and individual guidance, and continuous evaluation. The observed changes included greater fluency in recitation, improved understanding of the sequence of the pillars, more orderly movements, and increased student readiness, discipline, and responsibility. Support from the school principal, teacher collaboration, school culture, and periodic evaluation strengthened the program’s implementation, whereas time constraints, variations in ability, and differences in home-based guidance, as perceived by teachers and students, constituted barriers. Student development was not uniform and could not yet be causally attributed to the program. Originality/Value – This study explains salat instruction as a pedagogical and institutional process that connects the indicators of moral knowing, moral feeling, and moral action with immediate correction, formative assessment, and differentiated guidance. Practical Implications – Elementary schools with comparable characteristics may consider allocating dedicated time, distributing responsibilities, using observable indicators, documenting student progress, and providing remedial instruction, enrichment, and communication based on family needs.